HUBUNGAN ANTARA PENGASUHAN ISLAMI DENGAN IDENTITAS DIRI PADA REMAJA DI KOTA YOGYAKARTA - Early Maghfiroh Innayati (UIN Sunan Kalijaga Yogyakarta, 2012)
This research was aimed to determining the relationship between Islamic adolescent rearing practices with self identity and the different self identity between boys and girls. Several hypothesis were set as follow was : (1) there is a relationship between Islamic adolescent rearing practices with self identity, (2) there is a difference between boys and girls in terms of self identity.The subject involved 200 adolescent ; 110 boys and 90 girls, using purposive random sampling. The data were obtained by using Islamic adolescent rearing ractices scale (SPI) and self identity scale (SID). Data analysis used product moment and t-test.The first hypothesis was analysis using product moment. The result shows that Islamic adolescent rearing practices influenced self identity (r=0,549 ; =0,000). The second analysis showed that there was not a significant differences of self identity between boys and girls (t=-0,497 ; p=0,620), although mean value self identity of girls (210,25) was higher than boys (208,26).